Enhanced thermoelectric performance in n-type polycrystalline SnSe by PbBr2 doping. Issue 29 (23rd March 2017) - Li, Debo; Tan, Xiaojian; Xu, Jingtao; Liu, Guoqiang; Jin, Min; Shao, Hezhu; Huang, HuaJie; Zhang, Jianfeng; Jiang, Jun
Abstract : By increasing the carrier concentration and the DOS effective mass, a ZT of 0.54 was achieved at 793 K. Abstract : A series of PbBr2 -doped polycrystalline SnSe samples were synthesized by melting and hot pressing. By PbBr2 doping, the carrier concentration of SnSe was increased to 1.86 × 10 19 cm −3 from 2.41 × 10 17 cm −3, resulting in an increased electrical conductivity of 40 ± 2 S cm −1 at 713 K while the undoped SnSe was only 5.1 ± 0.3 S cm −1 . Meanwhile, the PbBr2 -doped samples also exhibit a larger density of state effective mass (0.812 m 0 ). Therefore, a high power factor of 4.8 ± 0.5 μW cm −1 K −2 and a peak ZT of 0.54 ± 0.1 were achieved at 793 K perpendicular to the hot pressing direction.